Technical and geoinformational systems in mining : proceedings of the School of Underground Mining, Dnipropetrovs'K/Yalta, Ukraine, 2-8 October 2011 /: proceedings of the School of Underground Mining, Dnipropetrovs'K/Yalta, Ukraine, 2-8 October 2011. (2011) - Unknown
No abstract available